Sleep apnoea and risk of post-operative infection: beyond cardiovascular impact. Issue 4 (6th April 2017) - Martínez-García, Miguel Ángel; Chiner, Eusebi
Recent decades have seen the publication of numerous studies on the association between excessive sleep disordered breathing (SDB), particularly sleep apnoea, and an increase in cardiovascular morbidity and mortality. These studies have used a wide range of methodologies and criteria for patient inclusion. The results have been diverse, depending on the type of cardiovascular event or risk factor investigated, the patients' cardiovascular risk, the severity or type of the SDB, and the analysis of the primary and secondary prevention of cardiovascular events [1]. Sleep apnoea impacts negatively on different diseases beyond the cardiovascular sphere http://ow.ly/ZdOC309KHXD